Optimizing cancer treatment: the synergistic potential of CAR-T cell therapy and CRISPR/Cas9 - Amiri, Maryam; Moaveni, Amir Kian; Majidi Zolbin, Masoumeh; Shademan, Behrouz; Nourazarian, Alireza (Frontiers in Immunology, 2024)
Optimizing cancer treatment has become a pivotal goal in modern oncology, with advancements in immunotherapy and genetic engineering offering promising avenues. CAR-T cell therapy, a revolutionary approach that harnesses the body's own immune cells to target and destroy cancer cells, has shown remarkable success, particularly in treating acute lymphoblastic leukemia (ALL), and in treating other hematologic malignancies. While CAR-T cell therapy has shown promise, challenges such as high cost and manufacturing complexity remain. However, its efficacy in solid tumors remains limited. The integration of CRISPR/Cas9 technology, a powerful and precise genome-editing tool, also raises safety concerns regarding unintended edits and off-target effects, offers a synergistic potential to overcome these limitations. CRISPR/Cas9 can enhance CAR-T cell therapy by improving the specificity and persistence of CAR-T cells, reducing off-target effects, and engineering resistance to tumor-induced immunosuppression. This combination can also facilitate the knockout of immune checkpoint inhibitors, boosting the anti-tumor activity of CAR-T cells. Recent studies have demonstrated that CRISPR/Cas9-edited CAR-T cells can target previously untreatable cancer types, offering new hope for patients with refractory cancers. This synergistic approach not only enhances the efficacy of cancer treatment but also paves the way for personalized therapies tailored to individual genetic profiles. This review highlights the ongoing research efforts to refine this approach and explores its potential to revolutionize cancer treatment across a broader range of malignancies. As research progresses, the integration of CAR-T cell therapy and CRISPR/Cas9 holds the promise of transforming cancer treatment, making it more effective and accessible. This review explores the current advancements, challenges, and future prospects of this innovative therapeutic strategy.